Rehabilitacija bolnikov po odstranitvi očesa zaradi tumorja - Drnovšek-Olup, Brigita (Rehabilitacija (Ljubljana), 2008)
The article discusses rehabilitation of ophthalmic patients with eye tumors, from surgical intervention to final care of a patient with eye prosthesis. It describes the surgical procedure and the phases of rehabilitation after surgery to the final insertion of the eye prosthesis. The removal of an eyeball (enucleation) represents both physical and psychical trauma to the patient. The visual function is affected, which limits the patient in performing everyday activities, and his body image is changed. The main purpose of the surgical treatment and subsequent rehabilitation is to limit the progress of the malignant disease and to re-establish a quality lifestyle in the shortest possible time.
Keywords: enukleacija; kirurško zdravljenje; očesna proteza; oko; proteze; rak (medicina)